2021
DOI: 10.1016/j.jbc.2021.100981
|View full text |Cite
|
Sign up to set email alerts
|

Sequence variation in the β7–β8 loop of bacterial class A sortase enzymes alters substrate selectivity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(79 citation statements)
references
References 50 publications
7
72
0
Order By: Relevance
“…In general, the binding site for the P1' position in spySrtA does not appear to be particularly selective, which is consistent with our previous work on S. pneumoniae SrtA (9,15). Due to the observed similarities in these Streptococcus SrtA proteins, as well as our previous work investigating the 7-8 loop in these proteins, we hypothesize that spySrtA is also non-selective at this position and can accommodate a wide variety of P1' amino acids (9,23). Overall, the observed location for the P1' Ser, as well as the adjacent P1 Thr, renders the LPATS peptide ideally positioned for nucleophilic attack by the catalytic cysteine residue.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 91%
See 2 more Smart Citations
“…In general, the binding site for the P1' position in spySrtA does not appear to be particularly selective, which is consistent with our previous work on S. pneumoniae SrtA (9,15). Due to the observed similarities in these Streptococcus SrtA proteins, as well as our previous work investigating the 7-8 loop in these proteins, we hypothesize that spySrtA is also non-selective at this position and can accommodate a wide variety of P1' amino acids (9,23). Overall, the observed location for the P1' Ser, as well as the adjacent P1 Thr, renders the LPATS peptide ideally positioned for nucleophilic attack by the catalytic cysteine residue.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 91%
“…For Class A sortases, the general consensus sequence, which is found within the cell wall sorting signal (CWSS), includes a pentapeptide motif, Leu-Pro-X-Thr-Gly (or LPXTG), where X = any amino acid (4). Positions are defined with respect to the location of the cleavage site between the threonine and glycine residues, with P1' = Gly, P1 = Thr, P2 = X, P3 = Pro, and P4 = Leu (9). For proteinanchoring to the bacterial cell surface, the nucleophile in the second step of the reaction J o u r n a l P r e -p r o o f mechanism is the cell-wall precursor lipid II, thus allowing for incorporation of the protein into the growing peptidoglycan layer (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piper et al 137 have reported the effect of mutation in the β7–β8 loop region on the activity of SpSrtA. As discussed above, this enzyme is able to act on an LPX 1 TX 2 sequence where X 2 is Ala, Ser or Gly but the activity is otherwise relatively low.…”
Section: Enzyme Engineering To Broaden Substrate Scopementioning
confidence: 98%
“…Wojcik et al had previously shown that grafting the β7–β8 loop from SaSrtA into SpSrtA generated an LPXTG specific enzyme 138 however Piper et al investigated the effect of creating SpSrtA chimeras where the β7–β8 loop from SrtA from a variety of other Gram-positive bacteria was grafted into the SpSrtA backbone. 137 Many of these chimeras such as SpSrtA faecilis (in which three amino acid) substitutions were able to catalyse reaction of LPX 1 TX 2 peptide substrates faster than SpSrtA. Most interestingly, some of these enzymes were also able to act on a wider range of amino-acid nucleophiles including SpSrtA faecilis which was shown to act on a LPXTV sortase recognition sequence.…”
Section: Enzyme Engineering To Broaden Substrate Scopementioning
confidence: 99%